Flow analysis along the runner and gating system of a casting process - Sulaiman, Shamsuddin; Keen, Tham Chee (Elsevier, 1997)
Simulation of molten metal flow along runner and gating system of pressure diecasting is carried out. Network analysis method is used for this simulation with the aid of a program written in FORTRAN language. This method is chosen to reduce the amount of computation needed. Analysis was done on runner and gating system with four gates. The angles of the branches leading to the gate and mould cavities are varied from 40° to 90°. This is to find out the pressure needed to be applied by the plunger of the injection system during the casting process and how branch angle of the runner and gating system affect it. Metal front movement will also be determined. The results of this study shows that smaller branch angle will require less pressure to fill the runner and gating system. The time required to fill the runner and gating system takes longer when smaller branch angle is used. Bend and large cross sectional area changes should be reduced as this leads to high pressure needed to be applied by the plunger. Larger time interval may be used without affecting the accuracy of the pressure calculated.